EFFECT OF ALLELOPATHIC POTENTIAL OF JOHNSON GRASS SORGHUM HALEPENSES L. ON GERMINATION AND GROWTH OF SOME CROPS AND RELATIVE INFLUENCE OF DIFFERENT SPECIES EXTRACTION ON SEED GERMINATION AND RIHZOM GROWTH OF JOHNSON GRASS - A.M. Sultan (Mesopotamia Journal of Agriculture)
Two pot experiments ware carried out at the college of Agric and Forestry , Mosuel Univ ,in summer growing season of 2000 to determine the allelopathic effect of Sorghum halepenses on seed germination and growth of Sesamum indicum , Vigna sinensis , Solanum melongena , Cucumis melo Reticulatus .While second experiment had to investigate the allelopathic impact of Cyperus esculentus , Glycyrrhiza glabra , Helianthus annus Eucalyptus camaldulensis , Citrus rotundus on seed germination and rhizomes growth of S.Halepenses.Data was subjected to the convertional analysis of complet Randomized Design C.R.D. Results indicated that the plumule , radical and seedling dry weight of different species had inhibited when it treated with the aqueous extraction of S.Halepenses rhizomes if it compared with with leaves vegetative extraction . On the other hand , the leaves of Citrus rotundus , Eucalyptus camaldulensis and Helianthus annus Were significantly effect on seed germination of S.halepenses . Root extraction of Glycyrrhiza glabra had stimulated effect and increased the plumule length and dry weight of S.halepenses while Eucalyptus camaldulensis , Citrus rotundus leaves had inhibitor effect on growth of S.halepenses .